(untitled) (Fiep Bulletin - online, 2015)
The aim of the study was to investigate physical exercise practice among maintenance technicians and some influences on their overall state of health. 436 technicians from a Brazilian airline were investigated. For data collection, a Stress Symptom Inventory and a questionnaire were applied to classify the levels of stress, physical exercise practice and sleep habits. The results showed that there is an important relationship between physical exercise practice and stress (p<0,05). Besides, findings showed that unfit workers have 1,63 more chance to develop symptoms of stress when compared to the fit ones. To conclude, it is important to point out that inactivity may be related to the worker’s stress.